Synthesis of unique phosphazane macrocycles via steric activation of C-N bonds - Shi, Xiaoyan (2020)
Herein we describe that oxidation reactions of the dimeric cyclophosphazanes, [{P(μ-NR)}2(μ-NR)]2, R = tBu (1), to produce a series of diagonally dioxidized products P4(μ-N tBu)6E2 [E = O (2), S (3), and Se (4)] and tetraoxidized frameworks. The latter display an unexpected C-N bond activation and cleavage to produce a series of novel phosphazane macrocyclic arrangements containing newly formed N-H bonds. Macromolecules P4(μ-N tBu)4(μ-NH)2O4 (5) and P4(μ-N tBu)3(μ-NH)3E4, E = S (6) and Se (7), dicleaved and tricleaved products, respectively, are rare examples of dimeric macrocycles containing NH bridging groups. Our theoretical and experimental studies illustrate that the extent to which these C-N bonds are cleaved can be controlled by modification of steric parameters in their synthesis, by adjusting either the steric bulk of the substituents in the parent framework or the size of the chalcogen element introduced during the oxidation process. Our findings represent new synthetic pathways for the synthesis of otherwise-elusive macrocycle arrangements within the phosphazane family.